2021
DOI: 10.12669/pjms.37.5.4017
|View full text |Cite
|
Sign up to set email alerts
|

The practice of Burch Colposuspension versus Mid Urethral Slings for the treatment of Stress Urinary Incontinence in developing country

Abstract: Objectives: To compare the effectiveness and complications of Burch colposuspension and Mid Urethral Slings (MUS) for the treatment of Stress Urinary Incontinence (SUI). Methods: We conducted a cross-sectional study of 162 patients who underwent surgery for SUI with Burch colposuspension (n=40), tension free vaginal tape (TVT) (n= 59) or transobturator tape (TOT) (n=63), from 2006 to 2014 at the Aga Khan University Hospital- Karachi. All three groups were assessed in terms of demographics, cure rates, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…However, there are still complications, and the most common intraoperative complications are bladder and vaginal perforations and hemorrhage [10]. There were no significant intraoperative complications in our study, as evidenced by Abrar et al [18] who conducted a cross-sectional study of 162 patients who underwent surgery for SUI with Burch colposuspension (n = 40), tension free vaginal tape (TVT) (n = 59) or TOT (n = 63), from 2006 to 2014 at the Aga Khan University Hospital in Karachi.…”
Section: Discussionsupporting
confidence: 70%
“…However, there are still complications, and the most common intraoperative complications are bladder and vaginal perforations and hemorrhage [10]. There were no significant intraoperative complications in our study, as evidenced by Abrar et al [18] who conducted a cross-sectional study of 162 patients who underwent surgery for SUI with Burch colposuspension (n = 40), tension free vaginal tape (TVT) (n = 59) or TOT (n = 63), from 2006 to 2014 at the Aga Khan University Hospital in Karachi.…”
Section: Discussionsupporting
confidence: 70%
“…This research offers clinical proof that supports the TVT method, suggesting it provides a similar level of efficacy to open colposuspension, but without entailing the complications associated with open surgery. More recent studies, conducted by Saida Abrar et al across eight years, show that although TVT is considered to be the gold standard in many respects, surgeons must remember that colposuspension remains a valuable surgical technique, often offering more than satisfactory efficacy [24]. Moreover, low-tension suburethral bands have their own complications, such as urinary retention, de novo detrusor instability, infection and erosion, chronic pelvic pain, dyspareunia, which can all persist in the long term [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…3 Most published studies compared BC with other surgical procedures for SUI, showing diverse conclusions regarding subjective cure rates on the long-term follow-up period. 11,12,17, 19 A systematic review and meta-analysis comparing data from different SUI procedures showed that in long-term followup, MUS and BC have equal subjective continence rates. 20 We found similar postoperative subjective cure rates at the first month, the sixth month, and 1st year, similar to Fusco et al 20 However, preoperative UDI-6 scores were higher in the open BC group.…”
Section: Discussionmentioning
confidence: 99%